ROLE OF BREASTFEEDING IN PREVENTING LONG-TERM METABOLIC DISORDERS: REVIEW - I. A. Belyaeva; L. S. Namazova-Baranova; T. V. Turti; E. P. Bombardirova; M. D. Mitish; T. V. Potekhina (Педиатрическая фармакология)
The literature review is dedicated to the preventive role of breastfeeding in preserving long-term health of individuals and the population in whole. The issue is urgent due to high prevalence of multifactor metabolic diseases (obesity, pancreatic diabetes, hypertonic disease etc.) in adolescents and adults; these socially significant have started to set on in younger persons in the recent years. The article presents results of the studies dedicated to the association between the nature of the infant's feeding and risk of metabolic pathology conducted in the recent decades in various countries. Most works put premature infants in the high risk group, as the diets involving special formulas contributing to "catching-up" growth of neonates with low birth weight are statistically significantly associated with high risk of long-term cardiovascular diseases. According to numerous studies, artificial feeding significantly increases the risk of excess weight and obesity, hypertonic disease and atherogenic dyslipidemia. Possible mechanisms of realization of hereditary susceptibility to metabolic disorders in the setting of artificial feeding are enhanced insulin burst paired with further development of insulin resistance; preventive role of breast milk is associated with the hormones therein, which program the individual's metabolism. Along with that, breastfeeding provides metabolic and immunological programming by means of forming optimal intestinal microbiota in a child. All the studies indicate importance of prolonged breastfeeding during infancy, which is why medical administrative support provided by medical personnel of medical and preventive facilities is important for preventing hypolactasia. District pediatricians and nurses not only control, but also organize the process of breastfeeding; when necessary, they recommend special devices intended to optimize lactation (breast pumps, nipple shields); if breast latching is not feasible – feeding with extracted breast milk using bottles and pacifiers reproducing natural breast sucking mechanism.